2023
DOI: 10.3390/plants12112090
|View full text |Cite
|
Sign up to set email alerts
|

Production and Fiber Characteristics of Colored Cotton Cultivares under Salt Stress and H2O2

Abstract: Salt stress reduces the yield and quality of colored fiber cotton production, but this problem can be mitigated by the foliar application of hydrogen peroxide in adequate concentrations. In this context, the objective of the present study was to evaluate the production and characteristics of fibers of naturally colored cotton cultivares under irrigation with low- and high-salinity water and leaf application of hydrogen peroxide. The experiment was carried out in a greenhouse under a randomized block design, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…However, it must be highlighted that the application of H 2 O 2 at concentrations of 25 and 50 µM increased the production components in plants subjected to water with an electrical conductivity of 0.3 dS m −1 . Similarly, Veloso et al [42] studied colored cotton cv. 'BRS Jade' grown under salt stress and observed that the application of 75 µM of H 2 O 2 increased the seed cotton and lint cotton weights under irrigation with 0.8 dS m −1 water.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be highlighted that the application of H 2 O 2 at concentrations of 25 and 50 µM increased the production components in plants subjected to water with an electrical conductivity of 0.3 dS m −1 . Similarly, Veloso et al [42] studied colored cotton cv. 'BRS Jade' grown under salt stress and observed that the application of 75 µM of H 2 O 2 increased the seed cotton and lint cotton weights under irrigation with 0.8 dS m −1 water.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the beneficial effect of H 2 O 2 at the concentration of 23 µM on NFP may be associated with its function of signaling molecule and protection against biotic and abiotic stresses [36]. Hydrogen peroxide can activate the defense system, contributing to a rapid adaptation of the plant to conditions unfavorable to its development [20,28].…”
Section: Discussionmentioning
confidence: 99%
“…Given the growing need to use brackish water in agriculture, especially in semi-arid regions, searching for strategies that enable such use has been a great challenge for the scientific community. Among the strategies, the use of hydrogen peroxide (H 2 O 2 ) stands out because, when applied at appropriate concentrations, it can contribute to reducing the harmful effects of salinity and enable agricultural cultivation [19,20]. Hydrogen peroxide is a reactive oxygen species (ROS), which acts as a key signaling molecule in mediating physiological and metabolic processes, alleviating the adverse effects of stress on plants by increasing the activity of antioxidant enzymes and membrane stability, which in turn increases plant's tolerance to abiotic stresses [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the seeds of these genotypes in a new production cycle will be more tolerant to water deficit. It is worth mentioning that the use of naturally colored fiber cotton genotypes can reduce production costs in the textile industry, since there is no need for dyeing, consequently reducing damage to human health and the environment [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%